Europeans' Happiness from an Egalitarian Perspective: More Equal Overall, but Often More Polarized Between Rich and Poor - Jan Delhey; Marcus Gercke (Social Indicators Research, 2025)
European countries have become more prosperous since 2000, but social and economic development has also become more crisis-prone and, in particular, characterized by growing economic inequality. From an egalitarian perspective, the question arises as to how this ambivalent situation has affected the distribution of subjective well-being and, in particular, the gap between rich and poor. Based on life satisfaction data for 27 countries from 10 waves of the European Social Survey (2002–2024), this paper examines whether well-being within nations has become more unequal, both in the populations as a whole (overall dispersion) and between income groups specifically (group polarization). For the total population, our results suggest that there is growing equality in life satisfaction almost everywhere, which is mainly driven by falling unemployment and increases in national prosperity. In about half of the countries, however, we find an increasing polarization of life satisfaction between rich and poor, fueled by rising national prosperity and increasing social protection expenditures. From an egalitarian point of view, the last two decades have thus brought both progress and regression.
Keywords: 300; Life satisfaction; Well-being; Happiness inequality; Polarization; Income groups; Trend analysis